2020
DOI: 10.1111/joop.12327
|View full text |Cite
|
Sign up to set email alerts
|

Rising above: Investigating employee exemplification as a response to the experience of shame induced by abusive supervision

Abstract: Scholars have clearly demonstrated that abusive supervision can precipitate a variety of destructive reactions from employees. Employees, however, do not universally reciprocate mistreatment with their own destructive behaviour and yet our current understanding of how victims of abusive supervision might choose to react less destructively, or potentially constructively, is still limited. Further, we lack a sufficient understanding of the psychological mechanisms that help explain why employees may react less d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 67 publications
(99 reference statements)
2
29
0
Order By: Relevance
“…The experience of shame initiates a desire to change one's image or reputation within a group in a proactive way (Bonner et al, 2017). Empirically, shame has been found to be positively associated with approach and prosocial behaviors (Kim et al, 2020;De Hooge et al, 2010). On the other hand, some researchers have revealed the maladaptive nature of shame and suggested that shame is expected to be linked with social withdrawal (De Hooge et al, 2018).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The experience of shame initiates a desire to change one's image or reputation within a group in a proactive way (Bonner et al, 2017). Empirically, shame has been found to be positively associated with approach and prosocial behaviors (Kim et al, 2020;De Hooge et al, 2010). On the other hand, some researchers have revealed the maladaptive nature of shame and suggested that shame is expected to be linked with social withdrawal (De Hooge et al, 2018).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, the first theoretical contribution of this study is thus its extension of the nomological network of shame as a salient self-conscious emotion. Previous studies have examined situations that trigger the experience of shame, including unethical behavior (Bonner et al, 2017), and abusive supervision (Kim et al, 2020), but have not particularly considered the characteristics of hospitality contexts yet. Among the various antecedents of shame, failing to achieve the expected results is one of the most prominent (Daniels and Robinson, 2019).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 3 more Smart Citations